Comparative Study of Hicrome Agar Medium with Conventional Culture System for the Isolation of Uropathogens - Nahar, S Gul; Hasan, M Bulbul; Khatun, Mst Rokeya; Ali, M Nawshad (TAJ: Journal of Teachers Association, 2018)
Objective: The present study was done to compare the performance of chromogenic agar medium and conventional culture media for the isolation and presumptive identification of uropathogen. Methodology: A total 300 sample were collected from Rajshahi Medical College Hospital, Bangladesh during January to June, 2008. Urine samples of the suspected UTI cases, showing pus cells >5/HPF on microscopic examination were included for urine culture simultaneously onto 2 conventional media (Blood agar and MacConkey agar) and chromogenic agar medium (HiCrome UTI agar medium). Results: Culture yielded 139 (46.33%) bacterial growth among them, 133 (44.33%) showed single organism and remaining 06 (2.00%) showed mixed growth of two organisms in different combinations. It is evident from the present study that both HiCrome UTI agar and Blood agar (BA) media supported growth of all 145 bacteria, while MacConkey (MAC) agar yielded 133(91.72%) bacterial growths. The rate of presumptive identification of the isolates was found significantly higher (97.24%) on HiCrome UTI agar when compared with the MacConkey agar (80.68%) and Blood agar (27.58%) media. Out of 91 E. coli isolated, 88(96.70%) could be identified differentially on HiCrome UTI agar medium in contrast to 85(93.40%) on MacConkey agar and only 06(06.59%) on Blood agar. Again, all 06 (100%) of the isolate-pairs of mixed growth were identified distinctly on HiCrome UTI agar, whereas both Blood agar and MacConkey agar media could revealed only 01(16.66%) of the polymicrobial growth. Conclusion: HiCrome UTI agar medium has been documented for its very high yielding rate, rapid presumptive identification of both single and polymicrobial growths with greater precision and avoidance of biochemical tests for further identification of uropathogens. Thus it can be recommended as primary urine culture medium to be used by the clinical microbiology laboratories. TAJ 2011; 24(2): 128-135